Breaking Free: The Fight for Equal Pay in the Prison Service (2008)
2008 "Breaking Free: The Fight for Equal Pay in the Prison Service", 2008, Morgan, Jenny Read the Notes by the Public and Commercial Services Union (below) to learn more about the background to the film.